8-10 year old footballers` movement coordination skills: customizable training model - Kostyunina, L. I.; Bagayoko, D.; Nikolaev, D. S. (Theory and Practice of Physical Culture, 2021)
Objective of the study was to test theoretical and practical design and benefits of a customizable movement coordination skills training model for the 8-10 year old football players individualized for their nervous system types.